Peranan Pemanduan Kapal dalam Upaya Mengurangi Resiko Kecelakaan Kapal di Perairan Wajib Pandu Tanjung Perak Surabaya - Capt Pantjadjatmika (Jurnal Pendidikan Manajemen Transportasi, 2024)
This study aims to determine the role of ship pilotage in the mandatory pilotage waters of Tanjung Perak Surabaya. Pilotage is a pilot activity in assisting the captain in processing the movement of the ship so that navigation can be carried out safely, orderly and smoothly, while the Pilot according to the Shipping Law no. 17 of 2008, has the following definition: A pilot is a nautical sailor who has met the requirements set by the government to carry out pilotage. The pilot as an extension of the harbor master in the field of shipping safety, the main priority is the shipping safety factor. While the company in this case is PT. Pelabuhan Indonesia III (Persero) is profit-oriented. By looking at the dominant pilotage function to assist ship movement, so that the ship can dock or leave the dock, jestler, pier, jetty, buoy or others that require a pilot can be carried out safely, smoothly and under control. For this reason, through this study it will be known how big the role of ship pilotage is in efforts to reduce the risk of ship accidents in the mandatory pilotage waters of Tanjung Perak Surabaya.